Success of orthodontic treatment of linguoverted mandibular canine teeth using a direct inclined plane appliance - Taylor, Leah; Liu, Lan; Goldschmidt, Stephanie (Frontiers in Veterinary Science, 2023)
This study evaluated the success rate of orthodontic treatment of linguoverted mandibular canines in dogs using a directly applied inclined plane device. Medical records were retrospectively evaluated from 11 veterinary dental specialty hospitals from 1999-2021. Malocclusion class included 41.7% class 1, 47.2% class 2, 6.9% class 3, and 4.2% class 4 respectively. Severity of linguoversion was mild in 7.6% of teeth, moderate in 33.9%, and severe in 58.5%. There was complete resolution of linguoversion in 71.2% of teeth, functional resolution in 25.4%, and failure in 3.4%. The median treatment time was 42 (11-174) days. Adjuvant orthodontic treatments were performed at the same time as the inclined plane in 45.7% of teeth, including active force orthodontics, extractions of non-strategic teeth, gingivectomy, and odontoplasty. While the inclined plane was in place, 31.4% of dogs required an anesthetized appliance adjustment, and at the time of appliance removal, complications occurred in 19.4% of dogs. Of the teeth that had initial resolution, 14.4% had rebound movement that required additional treatment. This study supports that acrylic inclined plane is a good treatment option for linguoverted mandibular canines with a 96.6% success rate within a median of 6 weeks. Yet, orthodontic retention may be necessary in these cases to avoid the need for additional therapies.